Social policies and redistribution in Brazil - Bernhard Leubolt (International Labour Organization (ILO), 2014)
This paper aims at analyzing the contribution of social policies to declining rates of income inequalities in Brazil since the 1990s. Based on a framework of historical institutionalism, Brazil is characterised as a traditionally patrimonial society, marked by the institution of slavery. Important ruptures occurred during democratization in the 1980 s, when social movements successfully fought for social rights which featured prominently in the democratic constitution of 1988. During the 1990s a contradictory confluence of these achievements and neoliberal reforms led to the promotion of "inclusive liberalism". From the mid-2000s onwards policies began to shift in the direction of "evelopmental welfare" combining active state interventionism in economic and social policies with targeted cash transfers. This combination avoided the pitfalls of "inclusive liberalism"and promoted a considerable reduction of social inequalities.
Keywords: 330; income distribution; social policy; social protection; social expenditure; political development; trend; Brazil